2006
DOI: 10.1002/ejoc.200600634
|View full text |Cite
|
Sign up to set email alerts
|

First Total Synthesis of the Bioactive Anthraquinone Kwanzoquinone C and Related Natural Products by a Diels–Alder Approach

Abstract: The first total synthesis of the novel anticancer agent kwanzoquinone C (1), an anthraquinone glycoside which has been isolated from extracts of the roots of orange daylilies(Kaempfer) (Hemerocallis fulva) is reported. The strategy involves the preparation of the tetrasubstituted 1,3‐butadiene 6 by an electrocyclic conrotatory ring opening of the cyclobutanone rac‐11, which is obtained by a [2+2] cycloaddition.Diels–Alder reaction of 6 with the juglone derivative 5 gives the bis‐benzyl‐protected anthraquinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The known compounds were identified as hongconin (1) (7) [3], 3-[2-(acetyloxy)propyl]-2-hydroxy-8-methoxy-1,4-naphthoquinone (9) [11], isoeleutherin (10) [1], erythrolaccin (11) [4], and 1,2-dihydroxy-8-methoxy-3-methylanthraquinone (15) [12]. Compounds 1, 3, 4, 5, 6, 7, 9, 10 and 11 had been previously isolated from E. americana.…”
Section: Resultsmentioning
confidence: 99%
“…The known compounds were identified as hongconin (1) (7) [3], 3-[2-(acetyloxy)propyl]-2-hydroxy-8-methoxy-1,4-naphthoquinone (9) [11], isoeleutherin (10) [1], erythrolaccin (11) [4], and 1,2-dihydroxy-8-methoxy-3-methylanthraquinone (15) [12]. Compounds 1, 3, 4, 5, 6, 7, 9, 10 and 11 had been previously isolated from E. americana.…”
Section: Resultsmentioning
confidence: 99%
“…Several anthraquinones added to this class of components were categorized as significant natural sources with these features. For example, glycosylated anthraquinone kwanzoquinone C isolated from the Kaempfer orange tree ( Hemerocallis fulva L.) is an interesting compound for cancer chemotherapy as it has been reported to block the growth of four different types of tumor cells (GI 50 = 3.8–7.5 µg/mL) [ 170 , 171 , 172 ]. This class of compounds has been and continues to be extensively researched due to its extensive range of biological properties.…”
Section: Potential Of Synthesized Derivatives Of Emodinmentioning
confidence: 99%
“…(c) A mixture of 2,4-dibromo-1-hydroxyanthraquinone 3 (1 mmol) and subsequent aryl boronic acid (4,(6)(7)(8)(9)(10)(11)(12) (2.2 mmol), Pd(PPh 3 ) 4 (10 mol %), Bu 4 NBr (1 mmol) and K 2 CO 3 (4 mmol) was stirred in toluene-water mixture (100 and 20 mL) at 100 • C for 4-6 h (TLC) in an argon flow. After cooling to 25 • C, the mixture was diluted with benzene (200 mL) and washed with water.…”
Section: Procedures For Suzuki-miyaura Reactionsmentioning
confidence: 99%
“…A brief literature survey revealed that the routes for the construction of anthraquinone core are primarily based upon five categories, such as Friedel-Crafts condensations of benzene derivatives with functionalized phthalic anhydrides or phthaloyl dichlorides [8], Hauser annulations of cyanophthalides with cyclohexenones [9], Diels-Alder reactions [10,11], cross-coupling reaction and transition metal-mediated reactions [5,12] and biomimetic aldol condensations [13]. However, some annulation processes suffer from serious limitations which include the poorly efficient, and require several synthetic steps, harsh reaction conditions or using of substrates that are synthetically demanding.…”
Section: Introductionmentioning
confidence: 99%